ChemInform Abstract: Stereoselective Transformations of (+)‐Abietic Acid into (+)‐Vitedoin B and (+)‐Negundoin A. Issue 44 (4th November 2014) - Tapia, Ruben; Bouanou, Hanane; Alvarez, Esteban; Alvarez‐Manzaneda, Ramon; Chahboun, Rachid; Alvarez‐Manzaneda, Enrique
Abstract Stereoselective synthesis of spirolactone (+)‐vitedoin B (I) is achieved in 14 steps and spiro enol ether (+)‐negundoin A (II) is obtained in 19 steps from commercially available abietic acid.